Public Toilet as A Destination Image - Risman Jaya; Andi Ade Zulkifli; Ismail Ismail (Politeknik Pariwisata Makassar, 2024)
This study aims to determine the role of public toilets as a destination image in the tourist attraction of Bara Beach in Bulukumba Regency. This study applies a qualitative method on the grounds that this qualitative research is appropriate to be used in determining real conditions in the field by utilizing descriptive methods. In the new normal era like today, every tourist attraction must be able to ensure that health protocols are still strictly and consistently implemented. One of them is the implementation of sanitation in public toilets in tourist attractions, including at Bara Beach, because this is considered to be able to make tourists who use the public toilet feel safe and comfortable. Bara Beach is one of the mainstay marine tourism attractions of South Sulawesi province, especially Bulukumba Regency. Throughout the year this beach is visited by many tourists, this is due to the extraordinary potential it has in the form of a very fine stretch of white sand and a very beautiful beach area, including the beauty of the sunset when the day is approaching nightfall. For this reason, the availability of decent and standard public toilets is very necessary, the completeness of public toilet facilities in Bara Beach must of course be in accordance with the standards. And in terms of cleanliness, it is also very necessary to maintain it well, considering that the public toilet will be used by visitors or tourists, both domestic and foreign tourists. The availability of public toilets in Bara beach destinations will certainly not necessarily be a service solution for one of the basic needs of tourists, but what is no less important in this case is how to manage it. The management of public toilets must be done properly so that the needs of tourists for clean, comfortable and safe public toilets are met, but in addition to maintaining the cleanliness of public toilets can be maintained properly, the participation of users in this case tourists is also very much needed. For this reason, through this study, the researcher intends to further study